The effect of γ matrix channel width on the compositional evolution in a multi-component nickel-based superalloy. (October 2022) - Saksena, Aparna; Kubacka, Dorota; Gault, Baptiste; Spiecker, Erdmann; Kontis, Paraskevas
Abstract: High-temperature diffusion affects the long-term stability of superalloys and hence their service life. Yet, details of the mechanisms remain elusive. Here, the γ-γʹ microstructure itself is used as a nanoscale diffusion couple to study the diffusion of alloying elements within narrow and wide γ channels during annealing for up to 100 h at 750 °C in a nickel-based superalloy. Predictions from thermodynamic and kinetic calculations are compared to near-atomic experimental measurements as a function of the γ channel width. An overlooked width-dependence of compositional evolution is revealed that may directly affect the microstructural and compositional predictions of service life of nickel-based superalloys. Graphical abstract: Image, graphical abstract